Robotic-assisted bronchoscopic localization for small pulmonary nodules: a novel approach to minimally invasive surgery - Yu, Qiduo; Yang, Haoshuai; Chen, Jingyu; Kong, Fanjia; Zhang, Jin; Tian, Zhoujunyi; Zhang, Zhenrong; Liang, Chaoyang (Frontiers in Surgery, 2025)
BackgroundPrecise intraoperative localization of small pulmonary nodules is crucial for minimally invasive lung surgery. Robotic bronchoscopy, combining electromagnetic navigation and fluorescence marking, addresses limitations of traditional methods.MethodsThis feasibility study included 10 patients (mean age 58) with ground-glass/partially solid nodules (mean diameter 1.42 cm). Using the Monarch® robotic system, nodules were intraoperatively marked with fluorescent dye (indocyanine green/methylene blue). Segmentectomy (4) or wedge resection (6) was performed, with lobectomy added if needed.ResultsAll nodules were successfully localized (mean time 16.9 min) without complications. Resected specimens confirmed central nodule placement. Pathology identified primary lung cancer in all cases: 1 adenocarcinoma in situ, 3 microinvasive, and 6 invasive. Lobectomy was avoided in 4 segmentectomy cases but required in 5/6 wedge resections.ConclusionRobotic bronchoscopic localization enables safe, precise intraoperative marking, minimizing healthy tissue resection. This pilot study supports its clinical potential, warranting larger trials for validation.